Physical and Methodological Errors in the Works of Landau (Global Journal of Science Frontier Research, 2018)
By all is well known this phenomenon as rainbow. To any specialist in the electrodynamics it is clear that the appearance of rainbow is connected with the dependence on the frequency of the phase speed of the electromagnetic waves, passing through the drops of rain. J. Heaviside R. Vul assumed that this dispersion was connected with the frequency dispersion (dependence on the frequency) of the dielectric constant of water. Since then this point of view is ruling. However, this approach is physical and methodological error, that also is shown in this article. This error occurred because of the fact that during the record of current in the material media they were entangled integral and the derivative of the harmonic function, which take the identical form and are characterized by only signs.
Keywords: plasma; dielectric; dielectric constant; the dispersion of dielectric constant; harmonic function